Irrigation effect on wheat crop productivity - Tubelis, Antônio; Souza, Fernando Goulart de Andrade e (Pesquisa Agropecuaria Brasileira, 2014)
This paper deals with the effect of supplemental irrigation on the final productivity of wheat crop. It is based on an experiment having a variable duration of irrigation periods. All the periods started at the sowing date. The experiment was installed at Botucatu, São Paulo State, Brazil, on shallow, flat, purple latosol, without fertilizer and without liming, using the BH 1146 cultivar. The crop was grown under good climatic conditions having completed its cycle within 118 days. Final yield of the crop was correlated with the height of applied water in periods whose duration varied from 20 until 110 days. Forty-nine simple, linear equations between the height of applied water and the yield of wheat grain were obtained. Variation of wheat crop yield caused by the increase of 1 mm in the height of applied water was studied. A 767.7% - index of variation in the water profitableness ratio was observed. The increment of crop yield by the application of 1 mm of water height in each ten days of duration of concerned period was analysed. The crop yield increments showed a variation of 600.5%. At last, the level of irrigation was estimated to obtain certain wheat crop yields.